New composites from waste: iron ore, pulp, lime, and concrete - Pedroso, Cleber Luis; Mymrine, Vsévolod; Bavastri, Elizabete Yukiko Nakanishi; Pedroso, Daniela Evaniki; Neto, Alfredo Iarozinski; Catai, Rodrigo Eduardo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
This research aimed at the development of new composites for civil construction using only industrial waste, namely, iron ore tailings (IOT), pulp production waste (PPW), lime production waste (LPW), and concrete waste (CW). The characterization of raw materials was carried out through particle size, specific mass, hydrogen potential (pH), loss on ignition (LOI) tests, and scanning electron microscopy (SEM); and, it was analyzed axial compression resistance and SEM in the developed composites. The specimens for the resistance test were molded, always using the same four types of residues in the mixture, with only water addition and no other type of binder. The residues proportions used were, in percentage, 10% to 40% of IOT and PPW, 25 to 30% of the LPW, and 15% to 25% of CW, distributed in 19 different compositions, that is, the proportions' variation of the residues in each specimen. The specimens were tested at the ages of 3, 7, 14, 28, 60, 90, 180, 365, and 720 days of cure. The results indicated a slight increase in resistance with increasing curing time, with emphasis on compositions 16 and 17, whose 28-day axial compression resistance reached 4.07MPa and 6.92MPa, respectively. In these two compositions (16 and 17), the formation of new structures was observed in the materials due to the neutralization and dissolution of the surfaces, as the alkalinity gradually decreased over time, with the hydrogen potential (pH) around 7.50 that, consequently caused the synthesis of new amorphous and crystalline formations. In this context, the studies allowed to conclude that the association of industrial residues has potential use as civil construction materials, for instance, in concrete artifacts, besides contributing to the reduction of finite natural resources extraction. It also provides a correct destination for the waste disposed of inappropriately, that constantly menaces the environment and the society that lives around it.